Meningkatkan Kreatifitas Peserta Didik Dengan Menerapkan Pbl Dalam Pembelajaran Pakbp Kelas III Tema 1 Sub 1 Materi 1 Sekolah Dasar Negeri 101857 Gunung Rintih - Nopriani Barus; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to explore and analyze the application of problem-based learning (PBL) models in improving the creativity of grade 3 students at SDN 101857 Gunung Rintih. In the current educational context, it is important for students to not only receive information, but also develop critical thinking skills and creativity that can help them face challenges in the real world. The PBL model is designed to invite students to be actively involved in the learning process by identifying real problems that are relevant to life. Through a series of structured activities, students are encouraged to work in groups, discuss ideas, and find solutions together. This approach not only strengthens students' analytical abilities but also builds social and collaborative skills that are important for their development. In this study, data collection methods will involve observation, interviews, and questionnaires to assess the increase in students' creativity and problem-solving skills. It is hoped that the results of this study will show that the application of PBL can significantly improve students' creativity and facilitate their growth in academic and social aspects. These findings are expected to contribute to the development of more effective curriculum and learning practices at the elementary education level.